2017
DOI: 10.3945/jn.116.239475
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2-Antioxidant Signaling by 1,25-Dihydroxycholecalciferol Prevents Leptin-Induced Oxidative Stress and Inflammation in Human Endothelial Cells

Abstract: Obesity is associated with hyperleptinemia and endothelial dysfunction. Hyperleptinemia has been reported to induce both oxidative stress and inflammation by increasing reactive oxygen species production. The objective of this study was to determine the effects of 1,25-dihydroxycholecalciferol [1,25(OH)D] against leptin-induced oxidative stress and inflammation in human endothelial cells. Small interfering RNA (siRNA) were used to knock down the expression of vitamin D receptor (VDR) in human umbilical vein en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 40 publications
3
61
0
5
Order By: Relevance
“…Alternatively, VEGF may be coaxing MCs and Mϕs into differentiating to an EC fate. There is a growing body of literature suggesting that MCs may be capable of differentiating into EC‐like cells that express both MC/Mϕ markers and EC markers in vitro (56, 57, 7382). In agreement, our results revealed that the lumen of SHV grafts contained cells that expressed both M2‐Mϕ and EC markers, but in subluminal areas they expressed only Mϕ markers.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, VEGF may be coaxing MCs and Mϕs into differentiating to an EC fate. There is a growing body of literature suggesting that MCs may be capable of differentiating into EC‐like cells that express both MC/Mϕ markers and EC markers in vitro (56, 57, 7382). In agreement, our results revealed that the lumen of SHV grafts contained cells that expressed both M2‐Mϕ and EC markers, but in subluminal areas they expressed only Mϕ markers.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been established that 1,25(OH) 2 D 3 and 20(OH)L 3 protect against ROS formation [34,35,45]. In this study we tested vitamin D 3 and lumisterol metabolites:…”
Section: Novel Hydroxy-derivatives Of Vitamin D 3 and Lumisterol Redumentioning
confidence: 99%
“…A large body of clinical evidence has demonstrated the prevalence and risks of VD deficiency in various chronic disease and toxins induced tissue damage . In addition, studies have documented that VD activates the Nrf2 signaling pathway to ameliorate leptin‐induced oxidative stress and inflammation in human endothelial cells and regulate TGFβ/Smad signaling pathway in a murine model of asthma, but the mechanism is not clear …”
Section: Introductionmentioning
confidence: 99%